Cancer chronotherapy: Principles, applications, and perspectives - Mormont, Marie‐Christine; Levi, Francis (Cancer, 2003)
BACKGROUND Cell physiology is regulated along the 24‐hour timescale by a circadian clock, which is comprised of interconnected molecular loops involving at least nine genes. The cellular clocks are coordinated by the suprachiasmatic nucleus, a hypothalamic pacemaker that also helps the organism adjust to environmental cycles. The rest‐activity rhythm is a reliable marker of the circadian system function in both rodents and humans. This circadian organization is responsible for predictable changes in the tolerability and efficacy of anticancer agents, and possibly also may be involved in tumor promotion or growth. METHODS Expected least toxic times of chemotherapy were extrapolated from experimental models to human subjects with reference to the rest‐activity cycle. The clinical relevance of the chronotherapy principle (i.e., treatment administration as a function of rhythms) has been investigated previously in randomized multicenter trials. RESULTS In the current study, chronotherapeutic schedules were used to safely document activity of the combination of oxaliplatin, 5‐fluorouracil, and leucovorin against metastatic colorectal carcinoma and to establish new medicosurgical management for this disease, and were reported to result in unprecedented long‐term survival. CONCLUSIONS Chronotherapy concepts appear to offer further potential to improve current cancer treatment options as well as to optimize the development of new anticancer or supportive agents. Cancer 2003;97:155–69. © 2003 American Cancer Society. DOI 10.1002/cncr.11040 The concept of chronotherapy for cancer has been validated in Phase III clinical trials for the treatment of metastatic colorectal carcinoma and has provided novel perspectives for improving both the quality of life and clinical outcome of patients with advanced disease